'Art' in Archaeology and Anthropology: An Overview of the Concept. Issue 4 (11th September 2017) - Robb, John
Abstract : The concept of art has proved controversial in archaeology and anthropology. Many feel that the concept, developed to fit high art in modern Western society, is inappropriate for objects made for other uses, in other times, or in other cultures. Yet there is no widely agreed critique or alternative concept. This introduction reviews responses to this dilemma, ranging from using the concept uncritically, using the term 'art' simply as an archaeological convenience to refer to things such as petroglyphs and figurines, and treating art simply as material culture. It then explores the recent concepts of art as affective material culture, as socially defined networks, and as locally defined aesthetic action. Finally, it raises the possibility that art is our local category of the kind of powerful objects found in many cultures.